Rigorous discretization of subdivision techniques - Junge, Oliver (Equadiff 99)

Contention Resolution in Hashing Based Shared Memory Simulations - Czumaj, Artur; Meyer auf der Heide, Friedhelm; Stemann, Volker (SIAM Journal on Computing)

The computation of an unstable invariant set inside a cylinder containing a knotted flow - Dellnitz, Michael; Junge, Oliver; Rumpf, Martin; Strzodka, Robert (Equadiff 99)

Synthesis of Interfaces and Communication in Reconfigurable Embedded Systems - Eisenring, Michael; Platzner, Marco (IEE Proceedings -- Computers & Digital Techniques)

Toward embedded qualitative simulation: a specialized computer architecture for QSim - Platzner, Marco; Rinner, Bernhard; Weiss, Reinhold (IEEE Intelligent Systems)

Multi-class Linear Feature Extraction by Nonlinear PCA - Duin, Robert P.W.; Loog, Marco; Haeb-Umbach, Reinhold (International Conference on Pattern Recognition (ICPR 2000))
The traditional way to find a linear solution to the feature extraction problem is based on the maximization of the class-between scatter over the class-within scatter (Fisher mapping). For the multi-class problem this is, however, sub-optimal due to class conjunctions, even for the simple situation of normal distributed classes with identical covariance matrices. We propose a novel, equally fast method, based on nonlinear PCA. Although still sub-optimal, it may avoid the class conjunction. The proposed method is experimentally compared with Fisher mapping and with a neural network based approach to nonlinear PCA. It appears to outperform both methods, the first one even in a dramatic way.

Data-driven Phonetic Regression Class Tree Estimation for MLLR Adaptation - Haeb-Umbach, Reinhold (International Conference on Spoken Language Processing (ICSLP 2000))

LDA derived cepstral trajectory filters in adverse environmental conditions - Lieb, M.; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech, and Signal Processing (ICASSP 2000))
Amongst several data driven approaches for designing filters for the time sequence of spectral parameters, the linear discriminant analysis (LDA) based method has been proposed for automatic speech recognition. Here we apply LDA-based filter design to cepstral features, which better match the inherent assumption of this method that feature vector components are uncorrelated. Extensive recognition experiments have been conducted both on the standard TIMIT phone recognition task and on a proprietary 130-words command word task under various adverse environmental conditions, including reverberant data with real-life room impulse responses and data processed by acoustic echo cancellation algorithms. Significant error rate reductions have been achieved when applying the novel long-range feature filters compared to standard approaches employing cepstral mean normalization and delta and delta-delta features, in particular when facing acoustic echo cancellation scenarios and room reverberation. For example, the phone accuracy on reverberated TIMIT data could be increased from 50.7% to 56.0%
Keywords: acoustic echo cancellation algorithms; adverse environmental conditions; automatic speech recognition; cepstral analysis; cepstral features; cepstral mean normalization; command word task; delta-delta features; delta features; echo suppression; error rate reductions; feature vector components; FIR filters; LDA derived cepstral trajectory filters; linear discriminant analysis; long-range feature filters; phone accuracy; real-life room impulse responses; reverberant data; spectral parameters; speech recognition; standard TIMIT phone recognition task

Multi-class Linear Dimension Reduction by Generalized Fisher Criteria - Loog, M.; Haeb-Umbach, Reinhold (International Conference on Spoken Language Processing (ICSLP 2000))

Fuzzy dynamics: Methodological framework and applications of compartmental modeling - Hüllermeier, Eyke (in Proceedings CASYS-2000, 4th International Conference on Computing Anticipatory Systems Liège, Belgium)

In vitro-in vivo hepatic clearance prediction using fuzzy sets - Gueroguieva, I.; Nestorov, I.; Rowland, M.; Hüllermeier, Eyke (in Proceedings EUFEPS-2000, 6th European Congress of Pharmaceutical Sciences, Supplement 1)

In-line concentration measurement in complex liquids using ultrasonic sensors - Henning, Bernd; Daur, Peter-Christoph; Prange, Stefan; Dierks, Karsten; Hauptmann, Peter (Ultrasonics)
Recently there has been increased demand for chemicaJ sensors measuring in-line the concentration of selected substances in complex liquids in order to guarantee a high product quality in the process industry. At present there is a great interest in acoustic sensor systems for concentration measurements. This article presents a new ultrasonic sensor system consisting of a miniaturized multi-sensor arrangement for the comprehensive acoustic characterization of liquid mixtures. The sensor system measures sound velocity, impedance coefficient, attenuation coefficient an9 temperature.

Flexible control of case-based prediction in the framework of possibility theory - Dubois, D.; Hüllermeier, Eyke; Prade, H. (In Proceedings RàPC-2000, Raisonnement à partir de Cas, Toulouse, France)

Similarity-based inference as evidential reasoning - Hüllermeier, Eyke (In Proceedings ECAI-2000, 14th European Conference on Artificial Inteligence, Berlin, Germany)

Focusing search by using problem solving experience - Hüllermeier, Eyke (In Proceedings ECAI-2000, 14th European Conference on Artificial Inteligence, Berlin, Germany)

Investitionen, Realoptionen und Steuern unter Unsicherheit - König, Rolf; Sureth-Sloane, Caren (Das Wirtschaftsstudium)

The Influence of Taxation on Partially Irreversible Investment Decisions – A Real Option Approach - Sureth-Sloane, Caren

Change detection in heuristic search - Hüllermeier, Eyke (Proceedings AAAI 2000, 17th National Conference on Artificial Intelligence, Austin, Texas)

A method for predicting solutions in case-based problem solving - Hüllermeier, Eyke (in Proceedings EWCBR-2000, 5th European Workshop on Case-Based Reasoning, Trento, Italy)

Flexible control of case-based prediction in the framework of possibility theory - Dubois, D.; Hüllermeier, Eyke; Prade, H. (in Proceedings EWCBR-2000, 5th European Workshop on Case-Based Reasoning, Trento, Italy)